Effect of salt stress on free amino acid and polyamine content in cereals - Simon-Sarkadi, Lívia; Kocsy, Gábor; Sebestyén, Zoltán (Acta Biologica Szegediensis, 2002)
The effect of salt stress on the level of free amino acids and polyamines in cereal samples was investigated. Different cereal seedlings were exposed to 0.1 M NaCl. Quantitative determination of amino acids and polyamines were accomplished by chromatographic methods. The results showed genotype dependent changes in free amino acid and polyamine contents. The salt stress caused increases in proline, glutamic acid, aspartic acid, arginine, ornithine and γ-amino-butyric acid levels. With respect to polyamine content, salt stress increased the levels of putescine and decreased the concentration of spermidine.